2014
DOI: 10.1155/2014/125258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Distribution and Population on Maize (Zea maysL.) Grain Yield

Abstract: Maize planting is normally accomplished by hand in the developing world where two or more seeds are placed per hill with a heterogeneous plant spacing and density. To understand the interaction between seed distribution and distance between hills, experiments were established in 2012 and 2013 at Lake Carl Blackwell (LCB) and Efaw Agronomy Research Stations, near Stillwater, OK. A randomized complete block design was used with three replications and 9 treatments and a factorial treatment structure of 1, 2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
1
14
0
3
Order By: Relevance
“…This results in multiple seeds that emerge, non-uniform germination, seed rotting due to deep planting and loss of viable seed due to improper covering (Aikins et al, 2010). Chim et al (2014) reported that placing 1 instead of 2 or 3 seeds per hill could increase yields by 40%. Planting maize with the hand planter was advantageous, when compared to traditional planting practices.…”
Section: Hand Planter Importancementioning
confidence: 99%
“…This results in multiple seeds that emerge, non-uniform germination, seed rotting due to deep planting and loss of viable seed due to improper covering (Aikins et al, 2010). Chim et al (2014) reported that placing 1 instead of 2 or 3 seeds per hill could increase yields by 40%. Planting maize with the hand planter was advantageous, when compared to traditional planting practices.…”
Section: Hand Planter Importancementioning
confidence: 99%
“…Limited resources, terrain and precedence largely dictate farmer practice of planting density throughout the developing world but current practice in many regions of SSA, Central and South America and Asia is to hill seed (2-4 seeds per hill) at an average of 35 cm apart (Chim et al, 2014). As such, an objective of this study was to compare grain yield to differences in established plant populations from single-seed planting.…”
Section: Experimental Site and Designmentioning
confidence: 99%
“…While demand for corn in developing countries remains high (Borlaug, 2007;Shiferaw et al, 2011), its yields in developing countries are lower than in developed countries (Cairns et al, 2013;Chim et al, 2014). For example, since 1961 corn yields in the top five corn producing countries in the world (U.S.A., China, Brazil, Mexico, and Indonesia) have increased three-fold (from 1.84 Mg ha -1 to more than 6.10 Mg ha -1 ) while in developing regions of Africa, Asia, and Latin America, corn yields have stagnated at less than 2 Mg ha -1 (FAO, 2011;Cairns et al, 2013).…”
Section: Introductionmentioning
confidence: 99%